Evolução sem Destino: O Confronto dos Evolucionismos e a Contribuição Crítica de Thorstein Veblen à Ciência Política - Burglin, Patrick (2014)
It is described here how, during the second half of the nineteenth century, the Evolutionism drew attention to changing processes in nature and society not yet considered as such. Strictly speaking, there are two Evolutionary thoughts, who followed different and even opposite paths: while Darwin´s evolutionary theory outgrew scientific controversy in Natural History into the public opinion, Herbert Spencer´s evolutionary philosophy, influenced by the ideas of Lamarck, caught public attention, and then get scientific recognition, especially but not exclusively in the Social Sciences. While convergence of both get the public familiar with scientific reasoning, it had, on the other hand, the unfortunate consequence of confusing the naturalism advocated by Darwin as scientific approach, with the Naturalist Fallacy and Biological Determinism proposed by Spencer, resulting in "Social Darwinism," a supposedly scientific grounded policy. Thorstein Veblen, not entirely well succeeded in criticizing Spencer´s anti-socialist and anti-statist arguments, would be more successful when attacking the preconceptions of classical economic theory at its base. "Natural Rights" and utilitarian hedonism were fixed institutional framework and concept of human nature incompatible with the new perception of development processes brought about by Darwinian evolutionary theory. It was so possible to criticize, as Pre-Darwinian, the evolutionary philosophy, authored by Spencer. And it is from this criticism that Thorstein Veblen produced his own version of evolutionary science who, although aimed to Economics, would constitute, as shown here, a major contribution to Political Science.